Comparison of noise exposure among airport workers at two selected states - Halim, Nur Hamizah (Universiti Sains Malaysia, 2015)
Previous study found that airport workers are exposed to risk of hearing damage due to noise. This study was aimed to determine and compare noise exposure level among aircraft workers at Sultan Abdul Halim Airport, Kedah and Sultan Ismail Petra Airport, Kelantan. Besides, comparison of noise exposure level between daytime and nigh-time at both airports was determined. Association between the numbers of aircraft operates and the noise level at both airports was also conducted. Area noise levels at the terminal were measured using a sound level meter. The aircraft noise was recorded at 6 sampling points where the first point was 5 m distance from the noise source to 30 m. Based on the findings, workers at Sultan Ismail Petra Airport, Kelantan have higher exposure to noise than workers at Sultan Abdul Halim Airport, Kedah with average 75.87 ± 3.75 dB(A). However, the noise level did not exceed the Permissible Exposure Limit [action level: 85 dB (A)] as stated under Factories and Machinery (Noise Exposure) Regulations 1989. By using Mann-Whitney test, there was no significant difference of noise exposure between workers at both airports. This might be due to noise that emitted from the same type of aircraft at both airports. In addition, there was a significant difference of noise level between day-time and night-time at Sultan Ismail Petra Airport, Kelantan (p=0.008). This is because of shorter flight time at night where several flights were seen landing at the same time. Through Spearman Correlation test, there was no association between number of aircraft operates and noise level at both airport. Meteorological factor and other background noise can influence noise level at the airport. Even though, the workers at both airports were not exposed to noise beyond the recommended limit, long term effect due to continuous exposure of noise cannot be underestimated. As a conclusion, employers are responsible to ensure a safe level of noise at the workplace by conducting regular noise monitoring and health surveillance to the workers.